Epilepsy: The Quintessential Pathology of Consciousness - Andrea Eugenio Cavanna; Fizzah Ali (Behavioural Neurology)
Alterations in consciousness are central to epileptic manifestations, and involve changes in both the level of awareness and subjective content of consciousness. Generalised seizures are characterised by minimal responsiveness and subjective experience whereas simple and complex partial seizures demonstrate more selective disturbances. Despite variations in ictal origin, behaviour and electrophysiology, the individual seizure types share common neuroanatomical foundations generating impaired consciousness. This article provides a description of the phenomenology of ictal consciousness and reviews the underlying shared neural network, dubbed the 'consciousness system', which overlaps with the 'default mode' network. In addition, clinical and experimental models for the study of the brain correlates of ictal alterations of consciousness are discussed. It is argued that further investigation into both human and animal models will permit greater understanding of brain mechanisms and associated behavioural consequences, possibly leading to the development of new targeted treatments.